Unruly media YouTube, music video, and the new digital cinema - Vernallis, Carol (Oxford University Press, 2013)
'Unruly Media' is the first book to account for the current audiovisual landscape across media and platform. It includes new theoretical models and close readings of current media as well as the oeuvre of popular and influential directors
Includes bibliographical references and index
Keywords: Digital media / Technological innovations; Music videos -- History and criticism; Digital media -- Technological innovations; YouTube; Media-Mix; Musikvideo; Neue Medien